Revealing the Intrinsic Peroxidase-Like Catalytic Mechanism of Heterogeneous Single-Atom Co–MoS2 - Wang, Ying; Qi, Kun; Yu, Shansheng; Jia, Guangri; Cheng, Zhiliang; Zheng, Lirong; Wu, Qiong; Bao, Qiaoliang; Wang, Qingqing; Zhao, Jingxiang; Cui, Xiaoqiang; Zheng, Weitao (Nano-Micro Letters, 2019)
The single-atom nanozyme is a new concept and has tremendous prospects to become a next-generation nanozyme. However, few studies have been carried out to elucidate the intrinsic mechanisms for both the single atoms and the supports in single-atom nanozymes. Herein, the heterogeneous single-atom Co–MoS2 (SA Co–MoS2) is demonstrated to have excellent potential as a high-performance peroxidase mimic. Because of the well-defined structure of SA Co–MoS2, its peroxidase-like mechanism is extensively interpreted through experimental and theoretical studies. Due to the different adsorption energies of substrates on different parts of SA Co–MoS2 in the peroxidase-like reaction, SA Co favors electron transfer mechanisms, while MoS2 relies on Fenton-like reactions. The different catalytic pathways provide an intrinsic understanding of the remarkable performance of SA Co–MoS2. The present study not only develops a new kind of single-atom catalyst (SAC) as an elegant platform for understanding the enzyme-like activities of heterogeneous nanomaterials but also facilitates the novel application of SACs in biocatalysis. Highlights: 1 Single-atom Co–MoS2 (SA Co–MoS2) is prepared successfully to serve as a proof-of-concept nanozyme model, which exhibits peroxidase-like performance comparable to that of natural enzymes. 2 The different mechanisms between the single-atom metal center and the support are investigated experimentally and theoretically.